2015
DOI: 10.1017/s0007114515000434
|View full text |Cite
|
Sign up to set email alerts
|

Patients undergoing elective coronary artery bypass grafting exhibit poor pre-operative intakes of fruit, vegetables, dietary fibre, fish and vitamin D

Abstract: CHD may ensue from chronic systemic low-grade inflammation. Diet is a modifiable risk factor for both, and its optimisation may reduce post-operative mortality, atrial fibrillation and cognitive decline. In the present study, we investigated the usual dietary intakes of patients undergoing elective coronary artery bypass grafting (CABG), emphasising on food groups and nutrients with putative roles in the inflammatory/anti-inflammatory balance. From November 2012 to April 2013, we approached ninety-three consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 78 publications
3
6
0
Order By: Relevance
“…It is important to highlight that although the text-messaging intervention improved adherence to the dietary guideline recommendations, the proportions of patients meeting the recommendations for consumption of vegetables, fruits and fish were still low, with less than 15% of patients achieving the recommendations for vegetables and less than 50% for fruits and fish at six-months follow-up. These results are similar to other studies showing low consumption of vegetables and fruits in people with CHD, [ 14 , 35 ] and are also comparable to the results of the Australian National Health Survey 2014–15, which showed that only 7.0 and 49.8% of the population are meeting the recommended daily consumption of vegetables and fruits, respectively. [ 36 ] In contrast, the proportion of patients that reported using unsaturated fat oils for cooking was already very high at baseline, similar to proportions shown in another study, [ 14 ] and hence unsurprisingly, there was no further improvement with respect to this variable.…”
Section: Discussionsupporting
confidence: 91%
“…It is important to highlight that although the text-messaging intervention improved adherence to the dietary guideline recommendations, the proportions of patients meeting the recommendations for consumption of vegetables, fruits and fish were still low, with less than 15% of patients achieving the recommendations for vegetables and less than 50% for fruits and fish at six-months follow-up. These results are similar to other studies showing low consumption of vegetables and fruits in people with CHD, [ 14 , 35 ] and are also comparable to the results of the Australian National Health Survey 2014–15, which showed that only 7.0 and 49.8% of the population are meeting the recommended daily consumption of vegetables and fruits, respectively. [ 36 ] In contrast, the proportion of patients that reported using unsaturated fat oils for cooking was already very high at baseline, similar to proportions shown in another study, [ 14 ] and hence unsurprisingly, there was no further improvement with respect to this variable.…”
Section: Discussionsupporting
confidence: 91%
“…Ruiz-Núñez et al [27] reviewed 55 patients undergoing CABG and found that dietary vitamin D intake was below the recommendations. The percentage was 13%, while the recommended dose was 10 to 20 µg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…[103][104][105] In addition, nutrition is a modifiable risk factor for systemic inflammation which ensues CHD, and its optimization may reduce post-cardiac surgery mortality, atrial fibrillation, and cognitive decline. 106 Dutch group showed that share of patients with CHD undergoing surgery with dietary intakes below recommendations were 62% for fruits, 87% for vegetables, 73% for dietary fiber, 98% for vitamin D, as well as patients with dietary intakes above recommendations were 95% for saturated fat. Unbalanced pre-operative diets put them at risk of unfavorable surgical outcomes, because they promote a pro-inflammatory state.…”
Section: Nrs In Ischemic Heart Diseasementioning
confidence: 99%
“…Unbalanced pre-operative diets put them at risk of unfavorable surgical outcomes, because they promote a pro-inflammatory state. 106 Undesirable changes in nutrition happens after CABG surgery with increase in fat consumption which occurred despite the provision of dietary advice and highlights the need to understand better the barriers to nutritional advices and education. 106,107 There have been a number of studies proving the prognostic effects of poor nutritional status and cardiac cachexia on CAD.…”
Section: Nrs In Ischemic Heart Diseasementioning
confidence: 99%